Seismic Pounding Response of Neighboring Structure using Various Codes with Soil-Structure Interaction Effects: Focus on Separation Gap - Ganesh Deoraoji Awchat; Amruta Monde; Rajat Sirsikar; Rahul Dingane; Gopal Dhanjode (Civil Engineering Journal, 2022)
Due to the high cost and less availability of land, the buildings are constructed adjacent to each other with a significantly smaller separation gap. Whenever seismic forces act on adjacent structures, they collide and cause significant structural and architectural damage. Soil-Structure Interaction (SSI) effects cause more complications in the adjacent structures. This paper assesses the gap distance between RC bare frame adjacent structures of varying heights in medium and soft soil with and without SSI to avoid the pounding effect of an earthquake. The main objectives are to find the separation distance between adjacent buildings by the provisions of FEMA 356, IS 1893 (Part 1):2002, IS 1893 (Part 1):2016 and EN 1998-1:2004. The separation gap between different codes was then compared to determine the minimum separation required to prevent pounding between the structures. The maximum lateral displacement on the roof and the time period of the adjacent buildings are compared with and without SSI. There is a significant increase in lateral displacement, separation distance, and time period considering SSI. It is found that the Indian code overestimates the separation distance. Thus, this study guides structural engineers to maintain a minimum separation distance between buildings erected on medium and soft soils in high seismic zones of India.Â Doi: 10.28991/CEJ-2022-08-02-09 Full Text: PDF